Paradox of Bureaucracy Neutrality in The Indonesia Regional Election - Tamma, Sukri (LP2M IAIN Palopo, 2016)
This paper aims provides how the actual issue of neutrality of Indonesian bureaucracy, especially on the Civil Servants of local government related to the Local election process. The important position of civil servants as public servants with its network touches many aspects of community life makes people as dependent on the bureaucracy existence. At the same time,bureaucracy seems under the politicians' interests due to their position in the system of regional government. This study also simultaneously shows how the concept of neutrality implements in Indonesian bureaucracy associated with the Indonesian political system, including in the context of the regional government.